Epigenetic regulation of regulatory T cells in patients with abdominal aortic aneurysm - Xia, Qian; Zhang, Jian; Han, Yanshuo; Zhang, Xiaoyu; Jiang, Han; Lun, Yu; Wu, Xiaoyu; Gang, Qingwei; Liu, Zhimin; Böckler, Dittmar; Duan, Zhiquan; Xin, Shijie (FEBS Open Bio, 2019)
Abdominal arterial aneurysm (AAA) shares many features with autoimmune diseases and appears to be a T-cell-mediated process. In addition, certain epigenetic changes, including DNA methylation, are associated with AAA. In this study, we investigated epigenetic modifications in regulatory T cells (Tregs) from AAA patients. We used flow cytometry to sort FOXP3+ CD4+ CD25+ Tregs from the peripheral blood of AAA patients and from healthy controls (HC), and then detected DNA methylation and histone modifications by ELISA. The DNA methylation rate of Tregs was significantly higher in AAA patients than in the HC group (0.159 ± 0.08% vs 0.098 ± 0.03%, P < 0.05), while the acetylation rates of H3 and H3K9 histones were lower in the AAA than in the HC group. We also examined the expression of mRNA encoding enzymes that catalyze making and removing epigenetic modifications by real-time PCR: we found that mRNA levels of DNA methyltransferase (DNMT) 1 and DNMT3A were higher in the AAA than in the HC group, mRNA levels of methyl-CpG-binding domain protein (MBD) 2 and MBD4 were higher in the AAA than in the HC group (MBD2: 6.21 ± 2.57 vs 3.04 ± 1.45; MBD4: 7.76 ± 3.48 vs 4.97 ± 3.10; both P < 0.05), and mRNA levels of histone deacetylase (HDAC) 1 and HDAC5 were significantly up-regulated in the AAA compared with the HC group (HDAC1: 2.17 ± 1.18 vs 1.51 ± 0.99; HDAC5: 1.35 ± 0.49 vs 0.94 ± 0.76; both P < 0.05). Together, our results reveal that rates of DNA methylation and histone modifications of Tregs are significantly altered in AAA patients.